Healthcare providers’ perspectives of the supportive care needs of women with advanced breast cancer in Ghana - Akuoko, Cynthia Pomaa; Chambers, Shirley; Yates, Patsy (BMC women's health, 2022)
Background The study sought to understand the supportive care needs of women with advanced breast cancer from the perspectives of healthcare professionals (HCPs) and key informants of charitable/non-governmental organisations (NGOs), that provide supportive care services to women with advanced breast cancer, in Ghana. Methods A qualitative descriptive approach was employed via one-to-one semi-structured interviews with 13 HCPs and key informants of charitable/NGOs in Ghana that provide supportive care services to women with advanced breast cancer. The study was underpinned by Bradshaw’s taxonomy of social needs and Fitch’s supportive care framework. The data were analysed using a deductive content analysis approach. Results Healthcare providers and key informants perceived that women with advanced breast cancer in Ghana have numerous and complex supportive care needs in key areas that align with Fitch’s supportive care framework, including informational, psychological, emotional, physical, practical, social, sexuality and spiritual needs. Conclusion Participants perceived that women who have advanced breast cancer in Ghana require ongoing information about their condition, treatments and related effects, as well as spiritual support and guidance particularly due to the fatalistic beliefs they often associate with the condition. Tailored supportive care interventions and services, which address the unique sociocultural circumstances for this cohort, are required. Additional research is needed to explore how multidisciplinary teams can work collaboratively to provide comprehensive support to women in addressing their needs.